PENINGKATAN NILAI TAMBAH UMKM KERIPIK SINGKONG MELALUI PENGUATAN HILIRISASI USAHA, BRANDING LOKAL, OPTIMALISASI PENGOLAHAN LIMBAH ORGANIK DI DESA CINDAI ALUS - Bayu Wicaksana; Afriza Afriza; Muhammad Rizal; Titis Diah Maharani; Rizka Fitri Rahmadhani; Abdullah Abdullah; Muhammad Ihsan; Jumrah Jumrah; Ade Yunike Octaviani; Risty Armayanti; Misbahul Abidin; Nadia Nurliana (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) producing cassava chips in Cindai Alus Village, Martapura District, Banjar Regency have significant economic potential, but their development still faces challenges such as low product added value, limited downstreaming, weak local branding, and suboptimal organic waste management. The ULM Berdampak Village Development program aims to increase the added value of MSMEs producing cassava chips by strengthening downstreaming, developing local branding, and optimizing organic waste processing. The implementation methods of the ULM Berdampak Village Development activity include problem identification and field surveys, socialization of activity programs, training and mentoring and activity evaluation. The ULM Berdampak Village Development activity has been successfully implemented to 36 (thirty six) people consisting of village government, PKK cadres, MSMEs of cassava chips, students implementing Village Development and field supervisors. The business downstreaming training was attended by 10 (ten) MSMEs of cassava chips and accompanied by students. Based on the training and mentoring, 5 (five) logos for cassava chip MSMEs were produced as branding for downstream products, 5 (five) banner designs for promotional media, and five (five) packaging designs, all of which have been used by the MSMEs. Evaluation results indicate that the branding mentoring activities have had a positive impact on improving the knowledge and skills of MSMEs. Ninety percent (90%) of participants stated they understand the importance of brand identity in increasing consumer trust, while eighty percent (80%) have begun implementing new packaging for their marketed products. Furthermore, training was conducted on processing cassava peel waste into compost and liquid organic fertilizer (POC). This training provided direct benefits in managing household waste that had previously been under-managed. Evaluation results indicate that the training successfully increased community understanding of the importance of organic waste management as part of sustainable downstream business processes. This increased knowledge is crucial for encouraging the implementation of zero-waste principles in cassava chip processing businesses.